2014
DOI: 10.5296/ijl.v6i1.4514
|View full text |Cite
|
Sign up to set email alerts
|

Death Euphemism in English and Arabic: A Conceptual Metaphorization Approach

Abstract: This study investigates and compares the conceptualization of death euphemism in English and Arabic as embodied in various euphemistic metaphors using the Conceptual Metaphor Theory initiated by Johnson (1980, 2003). It has been found, based on 442 euphemistic expressions in both languages (192 from Arabic, and 250 from English) that both languages use 10 strikingly similar complex conceptual metaphors to mitigate the effect of death, emanating from blending primary metaphors with cultural assumptions. The tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
0
8
0
2
Order By: Relevance
“…Galal (2014) conducted a study in which he compares the use of the euphemism for death in English and Arabic languages. The researcher found that implementing death euphemism in these two languages, English and Arabic, is almost the same since speakers of both languages tend to refer to death as a better life, a better location and so on.…”
Section: Euphemism In Arabic Studiesmentioning
confidence: 99%
“…Galal (2014) conducted a study in which he compares the use of the euphemism for death in English and Arabic languages. The researcher found that implementing death euphemism in these two languages, English and Arabic, is almost the same since speakers of both languages tend to refer to death as a better life, a better location and so on.…”
Section: Euphemism In Arabic Studiesmentioning
confidence: 99%
“…Death euphemisms in Arabic are also generally resistance euphemisms since death is a defeating human experience and one can only console oneself that after death the departed has been elevated to a better place as the favoured one (of Allah). Galal (2014) notes ten different connotation of death euphemisms in Arabic: death is a better location (e.g., ista'thar Allah-bih /God favored him), death is life (e.g., rafa'ah Allah 'ilayh / God raised the deceased to Him), death is a summoner (e.g., labba nida' rabbih / He answered his Lord's call), death is accomplishment of one's vow (e.g., qadha nahbah / He accomplished his vow), life is a robe that gets torn by death (e.g., tasharrama hablu hayatih / The robe of his life is torn off), death is a destination (e.g., madha lisabalih / (He) reached his destination), death is loss (e.g., ihtabalahu himamuh / His fate hunted him with a rope), death is regrouping and joining with God (e.g., laqiya rabbah / Met his Lord), death is surrender and submission (e.g., istaslama liqadha'ai Allah / He surrendered to God's destiny), and death is sleep (e.g., raqada raqdatahu al'akhirah / He slept his last sleep) (pp. 159-164)and it is worth noting that almost all the euphemisms reflect man's resistance to the inevitable but surrender to it because death is stronger than him, and self-consolation is the only alternative in the face of man's utter failure.…”
Section: Discussionmentioning
confidence: 99%
“…Kajian sebegini bukan sahaja diberi perhatian dalam penyelidikan luar negara, malah mendapat tempat di dalam negara juga. Misalnya, penyelidik-penyelidik seperti Muhammad Zaid, Mohammad Shahrul Nizam dan Remmy (2017, Hamidah, Imran Ho, Mohammed Azlan dan Khazriyati (2016), Siti dan Ernawita (2017), Galal (2014), Li-Na (2015), Ariffin, Djatmika dan Wiratno (2017), Danglli (2014), Eliya (2017) dan Harishon dan Phylisia (2012) telah menjalankan kajian mengenai fenomena berbahasa ini. Asmah (2008) menegaskan bahawa penggunaan eufemisme terdiri daripada kata yang bersifat berkias terhadap elemen yang dilihat negatif dan mampu memberikan kesan yang buruk terhadap emosi seseorang, alam dan sebagainya.…”
Section: 30 Sorotan Kajianunclassified